Experiences of Drug Addicts Undergoing Methadone Therapy towards Improved Quality of Life: A Case Study - Abu Shahim, Mohd Radhi; Md Shah, Kamarul; Md Shah, Kamarul; Arifin, Suhaili (Journal of Neonatal Surgery, 2025)
Methadone Therapy Treatment (MTT) also known as Replacement Therapy Treatment was first introduced in Malaysia in 2005 to help individuals achieve and maintain the recovery process from drug addiction symptoms and subsequently improve health and quality of life through healthy lifestyle practices. This qualitative study aims to explore the experiences of drug addicts undergoing Methadone Therapy Treatment (MTT) towards improving their quality of life. 10 respondents were selected using purposive and snowball sampling methods from the population of drug addicts undergoing Methadone Therapy Treatment (MTT) at one of the premises under the Malaysian Ministry of Health (KKM) that provides this treatment. Data was collected using a semi-structured interview technique guided by an interview protocol as a research instrument. The interview data obtained was transcribed and analyzed using the thematic analysis method with the help of NVivo10 analysis software. There are two main themes of the study results, namely the experience of undergoing treatment and issues related to treatment. The results of this study can explain the process of MTT and its implications for the target group as well as provide suggestions for improving MTT programs that are more effective, especially regarding the quality of life of drug addicts.